Acid Leaching Vermiculite: A Multi-Functional Solid Catalyst with a Strongly Electrostatic Field and Brönsted Acid for Depolymerization of Cellulose in Water - Xingtao Chen; Dongshen Tong; Zhi Fang; Zhenpeng Gao; Weihua Yu (Molecules, 2022)
Vermiculite is a natural mineral. In this study, vermiculite and acid-activated vermiculite was used as a solid acid catalyst for the hydrolysis of cellulose in water. The catalysts were characterized by XRD, FT-IR, and BET. The effects of time, temperature, mass ratio and water amount on the reaction were investigated in the batch reactor. The results showed that the highest total reducing sugars (TRS) yield of 40.1% could be obtained on the vermiculite activated by 35 (wt)% H2SO4 with the mass ratio of catalyst to cellulose of 0.18 and water to cellulose of 16 at 478 K for 3.5 h. The acid-activated vermiculite was a stable catalyst through calcination at 628 K and the yield of TRS decreased to 36.2% after three times reuse. The results showed that the crystal structure of vermiculite was destroyed and the surface -OH groups increased after the acid treatment. However, the synergistic effect of a strongly electrostatic polarization and Brönsted acid was responsible for the efficient conversion of cellulose. The mechanism of cellulose hydrolysis on the acid-activated vermiculite was suggested. This work provides a promising strategy to design an efficient solid catalyst for the cellulose hydrolysis, and expands the use of vermiculite in a new field.